Estudo das tendências e desenvolvimentos tecnológicos do carro elétrico no Brasil - Schiavi, Marcela Taiane (2020)
The present work has the purpose of conducting a survey of the studies on science and technology indicators of the automobile industry in relation to the electric car theme. It sought to analyze the monitoring of this market with Brazil as its central focus, however showing the market for this industry in other countries. For this, a typology was used in databases aimed at scientific articles, theses and dissertations and patents. Through the data of scientific indicators it was possible to analyze the current scenario, the trends, the future perspectives, key actors participating in the technological development process and to present the companies in their national and international scope. Some steps were necessary to carry out the entire process, namely: 1) a bibliographic survey where concepts and theories that involved this entire study are presented; 2) a survey of the patent database, where it was possible to analyze data on the development of the electric car in Brazil and other countries; 3) a survey of scientific articles and theses and dissertations that deal with the electric car and, consequently, analyze what has been studied on the subject, which countries publish more, among other analyzes and; 4) the last stage of this study focused on mapping the technological monitoring of the electric car in the country compared to other countries and analyzing the data obtained. The scenario of the automobile industry has been changing in recent years, giving less emphasis to the traditional combustion car and adopting the electric car as one of the options for sustainable mobility for society. In this research, a descriptive approach was used, since the study presents specific procedures for the elaboration and analysis of Science and Technology (S&T) indicators, structuring an overview of the trends and perspectives of the electric car in Brazil and in the world. Data collection was performed in the databases of the Digital Library of Theses and Dissertations on the Web of Science (WoS) and the Derwent Innovation Index (DII). From the results, it is emphasized that China is the largest producer of scientific publications in the world in relation to the electric car. Brazil, compared to other countries, has very few publications on the subject. As far as patent documents are concerned, we have only 2,115 registrations in the country so far, with Toyota holding the largest number, showing the need to reassess the country's concepts in relation to its priorities in this area.